دانانی بەرنامەیەکی فێرکاری پێشنیازکراو بۆ گەشەپێدانی لێهاتوییەکانی خوێندکارانی پەیمانگای هونەرە جوانەکانی چەمچەماڵ لە بابەتی داڕشتنی سیرامیک - حسین, سەرپەرشتیار: پ.د.جواد نعمت; احمد, توێژه‌ر: شوان محمود (Sulaimani Journal for Humanities, 2023)
Our research aim was to establish a proposed educational program for the development of the skills of students of Chamchamal Institute of Fine Arts in the Department of Arts on the drafting of ceramics, which according to the nature of the study and methods of methodology. Our research community also included a ceramic article for the fourth grade students of Chamchamal Institute of Fine Arts, for the academic year (2020-2021), as a result of reading and investigation, the researcher created an educational program according to the general model of research. The researcher used a survey tool that he distributed to the experts in order to implement the research curriculum correctly. This in itself was the result of the study. The study includes four parts, which consists of the first part of the study, the second part consists of the theory of the research and previous research and the framework consists of the following topics: - A Gateway to Ceramic Art - Contemporary Ceramic Art in Europe - Contemporary Ceramic Art in Iraq), The third part of the research consists of (research implementation procedures) and the last part, which is the fourth part of the research consists of (results, suggestions and recommendations) and then the list of sources.
Keywords: Keywords: Instructional design; ceramic sculpture